An Approximation of Inner Boundary Conditions for Wells Intersecting Highly Conductive Structures. Issue 4 (8th November 2019) - Giese, Markus; Reimann, Thomas; Liedl, Rudolf; Dewandel, Benoit; Maréchal, Jean‐Christophe; Sauter, Martin
Abstract: Inner boundary conditions describe the interaction of groundwater wells with the surrounding aquifer during pumping and are associated with well‐skin damage that limits water production and water derived from wellbore storage. Pumping test evaluations of wells during immediate and early time flow require assignment of inner boundary conditions. Originally, these concepts were developed for vertical well screens, and later transferred to wellbores intersecting highly conductive structures, such as preferential flow zones in fractured and karstic systems. Conceptual models for pumping test analysis in complex bedrock geology are often simplified. Classic analytical solutions generally lump or ignore conditions that limit or enhance well productivity along the well screen at the onset of pumping. Numerical solutions can represent well drawdowns in complex geological settings, such as karst systems, more precisely than many analytical solutions by accounting for additional physical processes and avoiding assumptions and simplifications. Suitable numerical tools for flow simulations in karst are discrete pipe‐continuum models that account for various physical processes such as the transient hydraulics of wellbores intersecting highly conductive structures during pumping. Abstract : Article impact statement : The numerical discrete pipecontinuum model MODFLOW‐CFPM1 simulates the effect of inner boundary conditions on drawdown in "extended wells".